Finance for the Plan - Planning Commission (Planning Commission, 1952)
The First Five-Year Plan of India, enacted in December 1952 with a financial allocation of Rs. 2,069 crore, focuses on enhancing national productivity, social justice, and employment. Emphasizing agriculture, irrigation, transport, industry, and social services, the Plan allocates 44.6% of resources to agriculture and irrigation to boost food production and rural development. Implementation strategies include mobilizing internal resources through savings, taxation, and loans, complemented by external aid from international financial institutions. Early progress reports (1952–53) indicate increased agricultural output, expanded irrigation, and growth in merchandise production, alongside major public-sector projects like the Bhakra-Nangal and Damodar Valley initiatives. Employment generation is addressed via public works, training programs, and work camps. The Plan underscores the importance of coordinated efforts among government, industries, and citizens, leveraging both domestic and foreign resources to achieve sustainable economic development and a prosperous future.
The Publications Division Ministry of Information and Broadcasting Government of India
The Publications Division Ministry of Information and Broadcasting Government of India
Keywords: First Five Year Plan; India; Public Sector Investment; Agriculture Development; Irrigation Projects; Social Services; Industrial Growth; Resource Mobilization; Employment Generation; Bhakra-Nangal Dam; Foreign Aid; Economic Planning